Performance Analysis of a Designed Prototype of a Motor Coupled Variable Inertia Flywheel System - Munimus Salam, Syed; Mahbubur Rashid, Muhammad (Malaysian Journal on Composites Science and Manufacturing, 2023)
The presence of a substantial moment of inertia in a flywheel poses challenges at the initiation of rotation in a rotating machine. During stable operation at high velocities, several energy-saving advantages can be efficiently attained, allowing for the potential of achieving adequate energy savings in specific applications. One potential solution to address this issue is the implementation of a flywheel that possesses the ability to modify its moment of inertia. While it is possible to derive the concept of variable inertia by adjusting the radii of the masses in relation to the axis of the flywheel, the techniques employed to regulate the variable inertial flywheel are rather intricate. This study presents an implementation of a variable inertia flywheel system coupling with electrical machinery to reduce power consumption. The main objective of the study is to reduce energy consumption utilizing variable inertia flywheel. Under various motion scenarios, the advanced machine’s dynamic reaction is examined. Finally, a standard testing method demonstrates almost ninety seven percent similarity between an analytical and practical analysis.